KESIAPAN KURIKULUM PENDIDIKAN AGAMA ISLAM BERSTANDAR PROSES DI PONDOK PESANTREN PUTERI UMMUL MUKMININ ‘AISYIYAH - Amri, Muh Ulil; Saprin; Muh Rusdi Rasyid (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LP2M) UIN Datokarama Palu, 2024)
This research aims to determine the readiness of the Islamic Religious Education (PAI) curriculum with standard processes at the Puteri Ummul Mukminin 'Aisyiyah Islamic Boarding School. This research includes qualitative descriptive research, with a phenomenological approach. Meanwhile, the data sources used in this research consist of primary and secondary data which begin with direct observations in the classroom guided by the observation guidelines that have been created, such as the interaction of teachers and students in Islamic religious education subjects, from the results of observations that have been carried out subsequently and conducted structured interviews with several Islamic religious education teachers and several students. In conducting interviews, researchers used tools, namely voice recorders and book notes, to help researchers verify and validate the validity and accuracy of the data by looking at comparative data from various sources that had been interviewed and then making interpretations and conclusions. The results of this research show that the readiness of the PAI curriculum is on the needs and development of students, especially at the Aliyah level of the Ummul Mukminin Girls Islamic Boarding School, which can be seen from several aspects such as relevance to educational standards, availability of teaching materials and implementation of learning which can provide feedback from students to gain meaningful experiences. It is hoped that the implications of this research can develop the curriculum in PAI subjects and other subjects.